The influence of technological parameters of deposition of multi-element ion-plasma coatings on its quality - E. N. Eremin; V. M. Yurov; V. C. Laurynas; A. Sh. Syzdykova (Омский научный вестник)
The technological parameters of deposition of high-entropy ionplasma coatings based on Kh18N10T alloyed steel by zirconium, copper and aluminum are studied. It has been established that with increasing evaporator arc current, the surface energy of the coating decreases, which is explained by a rapid increase in its thickness, leading to an increase in the dislocation density in the coating being formed. The optimal value of the arc current is 90–110 A. Coatings obtained at a nitrogen pressure of P=10–3 mm Hg. and the substrate temperature of 400 °C, have the most evenly distributed fine dense structure, the minimum content of the droplet phase, pores, influx, detachments, the highest values of surface energy and an increase in microhardness by 30 %.